2020
DOI: 10.1101/2020.02.28.20028902
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting the effect of statins on cancer risk using genetic variants: a Mendelian randomization study in UK Biobank

Abstract: Laboratory studies have suggested oncogenic roles of lipids, as well as anticarcinogenic effects of statins. We here assess the potential effect of statin therapy on cancer risk in Mendelian randomization analyses. We obtained genetic associations with the risk of overall and 22 site-specific cancers for 367,703 individuals in UK Biobank. In total, 75,037 individuals had a cancer event. Variants in the HMGCR gene region, which represent proxies for statin treatment, were associated with overall cancer risk (OR… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 71 publications
1
9
1
Order By: Relevance
“…In contrast to previous MR studies assessing overall cancer risk [29] and ovarian specific risk [30], the MR carried out here in relation to OC and OPC showed no effect using genetic instruments for HMGCR (statins). There was also limited evidence for a causal effect of NPC1L1 (ezetimibe), CETP (CETP inhibitors) as well as a number of other circulating lipid traits on OC or OPC.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…In contrast to previous MR studies assessing overall cancer risk [29] and ovarian specific risk [30], the MR carried out here in relation to OC and OPC showed no effect using genetic instruments for HMGCR (statins). There was also limited evidence for a causal effect of NPC1L1 (ezetimibe), CETP (CETP inhibitors) as well as a number of other circulating lipid traits on OC or OPC.…”
Section: Discussioncontrasting
confidence: 99%
“…The authors found little indication that statin therapy influences cancer incidence, which was consistent with the analyses of randomised trials (with a 10-year cancer-free survival difference of −0.3% 95%CI −1.5%, 0.5%) [19]. Nonetheless, recent MR studies [29,30] have identified an association between variants in HMGCR with cancer risk, but not alternative cholesterol-lowering treatments or genetically-predicted LDL-C, suggesting that statins may reduce cancer risk through a cholesterol independent pathway.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations